Molecular phenotypes of critical illness confer prognostic and biological enrichment in sub-Saharan Africa: a prospective cohort study from Uganda - Cummings, Matthew J; Lutwama, Julius J; Tomoiaga, Alin S; Owor, Nicholas; Lu, Xuan; Ross, Jesse E; Muwanga, Moses; Nsereko, Christopher; Nayiga, Irene; Nie, Kai; Kayiwa, John; Che, Xiaoyu; et al. (Thorax, 2025)
The generalisability of critical illness molecular phenotypes to low- and middle-income countries (LMICs) is unknown. We show that molecular phenotypes derived in high-income countries (hyperinflammatory and hypoinflammatory, reactive and uninflamed) stratify sepsis patients in Uganda by physiological severity, mortality risk and dysregulation of key pathobiological domains. A classifier model including data available at the LMIC bedside modestly discriminated phenotype assignment (area under the receiver operating characteristic curve (AUROC) 0.80, 95% CI 0.71 to 0.90 for hyperinflammatory vs hypoinflammatory; AUROC 0.74, 95% CI 0.65 to 0.83 for reactive vs uninflamed). Our findings highlight the potential for a globally relevant, clinicomolecular classification of critical illness and may support the inclusion of diverse populations in phenotype-targeted critical care trials. Improved laboratory capacity and access to rapid biomarker assays are likely necessary to optimise phenotype stratification in LMIC settings.